The genus Cittarium (Vetigastropoda: Trochoidea) in the Upper Miocene of the Dominican Republic with the description of a new species. (24th November 2015) - Landau, Bernard; Kronenberg, Gijs C.; da Silva, Carlos M.
Abstract: Today, the marine gastropod genus Cittarium is present only in the West Indies faunas, represented by a single species C . pica, also known from the Pleistocene of Bermuda. Herein Cittarium praepica n. sp. is described from the Upper Miocene Cercado Formation of the Dominican Republic. This is the oldest fossil record for the genus in the eastern Tropical America. The new species is compared to the Pleistocene to Recent Caribbean C . pica and to C . maestratii Lozouet, 2002 of the Upper Oligocene of France. The importance of this new record for the geological history and the biogeography of the genus are discussed.